DEVELOPMENT OF GENIALLY-BASED INTERACTIVE INFOGRAPHICS IN PUBLIC RELATIONS AND PROTOCOL SUBJECTS - Grasia, Ester; Faslah, Roni; Adha, Maulana Amirul (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
This study aims to determine the feasibility and practicality of learning media, namely Genially-based interactive infographics in the subject of OTK Public Relations and Protocol. This research was conducted on students of class XII OTKP at SMK Negeri 50 Jakarta. This research uses the Research and Development (RnD) method with the model development Analysis, Design, Development, Implementation, Evaluation (ADDIE). The data collection technique used a questionnaire with a likert scale of 1-5. The data analysis technique was carried out by expert validation test and practicality test. The results of this research show that Genially-Based Interactive Infographics in Public Relations and Protocol OTK Class XII SMK Negeri 50 Jakarta are declared very feasible and very practical and can be used in learning activities. This research contributes theoretically by expanding references on learning media through the development of interactive infographic media, while practically enabling the delivery of more engaging and effective information to students through the use of innovative technology.